Slavery and Other Forms of Strong Asymmetrical Dependencies Semantics and Lexical Fields - Bischoff, Jeannine; Conermann, Stephan (Dependency and Slavery Studies, 2022)
This volume approaches the phenomenon of slavery and other types of strong asymmetrical dependencies from two methodologically and theoretically distinct perspectives: semantics and lexical fields. Detailed analyses promise to provide new insights into the worldview of pre-modern societies. The case studies range from Ancient China and Egypt over Greek and Maya societies to Early Modern Russia, the Ottoman Empire and Islamic and Roman law